1986
DOI: 10.1038/ki.1986.28
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin-induced nephropathy as a model of chronic progressive glomerular disease

Abstract: Serial changes in urine protein, blood chemistry, and histology of the kidney were investigated in rats for 28 weeks after injections of adriamycin (ADR). Massive proteinuria, hypoalbuminemia, and hyperlipidemia were observed at week 4 and throughout the experiment. Both BUN and serum creatinine began to increase at week 16 and reached the uremic level at week 28. Light microscopic study of the kidney demonstrated a normal appearance at week 4, vacuole formation in glomerular tuft at weeks 8 and 12, focal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(194 citation statements)
references
References 11 publications
17
175
0
2
Order By: Relevance
“…A long term study demonstrated severe renal damage with extensive glomerular sclerosis and tubulointerstitial degeneration in ADR-treated rats (3). ADR-induced glomerulosclerosis in the rat is a progressive glomerulosclerosis model similar to human focal segmental glomerulosclerosis (3,4). In the advanced stages of the ADR model there is a severe interstitial infiltration of mononuclear cells (3), and in our preliminary experiments we found that there is also a significant infiltration of ␥␦ T cells in the ADR kidney (4).…”
Section: Infiltration Of Canonical V␥4/v␦1 ␥␦ T Cells In Anmentioning
confidence: 62%
“…A long term study demonstrated severe renal damage with extensive glomerular sclerosis and tubulointerstitial degeneration in ADR-treated rats (3). ADR-induced glomerulosclerosis in the rat is a progressive glomerulosclerosis model similar to human focal segmental glomerulosclerosis (3,4). In the advanced stages of the ADR model there is a severe interstitial infiltration of mononuclear cells (3), and in our preliminary experiments we found that there is also a significant infiltration of ␥␦ T cells in the ADR kidney (4).…”
Section: Infiltration Of Canonical V␥4/v␦1 ␥␦ T Cells In Anmentioning
confidence: 62%
“…Adriamycin causes well-described podocyte injury in rats (21), but its nephrotoxicity in mice is strain dependent. Balb/C mice are susceptible to podocyte injury by Adriamycin (22,23), whereas other strains that have been tested normally are resistant (24).…”
Section: Discussionmentioning
confidence: 99%
“…It offers the opportunity to study the effect of MSCs at various time points of the disease, model of nephrosis (2,24). Overall 55 rats were utilized, 14 for acute ADR, 33 for chronic ADR, and 8 were including a potential reparative effect when renal lesions have already developed.…”
Section: Mesenchymal Stem Cells In Chronic Adriamycin-induced Nephrosmentioning
confidence: 99%
“…ADR-induced renal failure is a well-accepted chronic Only cells between passage 4 and 10, positive for CD73, CD90, and CD105 surface markers (Pharmingen, disease model of progressive glomerulosclerosis in rats (1,2,24). It is characterized by rapid development of pro-BD Biosciences, Franklin Lakes, NJ, USA) and negative for CD45 (>95%) were utilized in all in vitro and in teinuria and glomerulosclerosis and evolves to renal fibrosis and renal failure.…”
Section: Introductionmentioning
confidence: 99%